2007
DOI: 10.1519/r-19845.1
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Ten Weeks of Lower-Body Unstable Surface Training on Markers of Athletic Performance

Abstract: Initially reserved for rehabilitation programs, unstable surface training (UST) has recently grown in popularity in strength and conditioning and general exercise scenarios. Nonetheless, no studies to date have examined the effects of UST on performance in healthy, trained individuals. The purpose of this study was to determine the effects of 10 weeks of lower-body UST on performance in elite athletes. Nineteen healthy, trained members (ages 18-23 years) of a National Collegiate Athletic Association Division I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
62
2
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 0 publications
3
62
2
3
Order By: Relevance
“…A recent study of simulated firefighting activities identified aspects of muscular strength, endurance, power, and abdominal strength related to performance but did not measure balance (Michaelides, Parpa, Henry, Thompson, & Brown, 2011). While the effects of physical training and performance on balance have been studied in athletes, it is unknown whether physical training mitigates the effects of TPC/SCBA on firefighters’ balance (Cressey, West, Tiberio, Kraemer, & Maresh, 2007; Filipa, Byrnes, Paterno, Myer, & Hewett, 2010). Therefore, we investigated potential relationships between physical characteristics and physical activity patterns on firefighters’ functional balance when wearing TPC and SCBA.…”
mentioning
confidence: 99%
“…A recent study of simulated firefighting activities identified aspects of muscular strength, endurance, power, and abdominal strength related to performance but did not measure balance (Michaelides, Parpa, Henry, Thompson, & Brown, 2011). While the effects of physical training and performance on balance have been studied in athletes, it is unknown whether physical training mitigates the effects of TPC/SCBA on firefighters’ balance (Cressey, West, Tiberio, Kraemer, & Maresh, 2007; Filipa, Byrnes, Paterno, Myer, & Hewett, 2010). Therefore, we investigated potential relationships between physical characteristics and physical activity patterns on firefighters’ functional balance when wearing TPC and SCBA.…”
mentioning
confidence: 99%
“…9-12 yaş 17 çocukta 6 haftalık haftada 3 kez uygulanan core stabilizasyon planı, tam mekik ve şınav gibi core testleri geliştirmiştir (Ahmadi, Hidari, Mahdavi, & Daneshmandi, 2014). Bu gelişim yalnız core stabilizasyon antrenmanları ile değil, diğer tipteki temel direnç antrenmanları ile de meydana gelmektedir (Cressey, West, Tiberio, Kraemer, & Maresh, 2007;Oliver & Di Brezzo, 2009; Schiffer, T., Kleinert, J., Sperlich, B., Schulte, S. and Stru der, 2009). Bu da core kasların izole çalışmaktan çok kinetik zincirdeki önemini ortaya koymaktadır.…”
Section: Bulgularunclassified
“…Training on unstable surfaces has recently become very popular in sports [27], and the training of MMA athletes is no exception. Videos uploaded on sites such as Youtube ® show MMA athletes employing instability implements in their training sessions.…”
Section: Training On Unstable Surfacesmentioning
confidence: 99%
“…Such effects have been observed acutely [27,30] and may lead to a chronic attenuation in the performance of specific tests such as countermovement jumps and displacement speed [27,29,30]. Chulvi-Medrano and colleagues [30] examined the force production and activity of paraspinal muscles in the deadlift exercise performed under stable conditions and later with the use of two instability implements, BOSU ® and T-Bow ® .…”
Section: Training On Unstable Surfacesmentioning
confidence: 99%
See 1 more Smart Citation